PENINGKATAN USAHA EKONOMI TRADISIONAL: STUDI KASUS PETANI MADU HUTAN DI DESANANGA LEBOYAN, KAPUAS HULU - Benedikta Juliatri Widi Wulandari (Pusbindiklat - LIPI, 2009)
This research presents the success story of the honey harvesters at Nanga Leboyan Village, Selimbau District, Kapuas Hulu Regency, West Kalimantan Province in improving their traditional economic activity. The aims of the study are to describe changes in techniques and treatments in honey business management and to explain the effects of the changes. Qualitative approach was applied in this study. Data collecting was conducted by applying participant observer and in-depth interview technique. Informants were selected based on snowballing method. The results of this research indicate that the changes in techniques and treatments in honey business management bring about positive impacts for the honey harvesters. The effects are: (1) Increasing of honey quality that cause increasing in the product price. (2) Mortality of honey bees becomes less that lead to increasing amount of honey that can be produced.